English Skills with Readings - Langan John (Mc Graw-Hill, 2007)
The new seventh edition of English Skills with Readings features John Langan's trademark crystal-clear explanations, along with his range of motivating activities and writing assignments that reinforce the four bases of effective writing: unity, support, coherence, and sentence skills. This edition of the book adds a variety of exciting new features to John Langan's proven approach, and reinstates much-requested materials from previous editions.